Thunderclap headache revealing dural tears with symptomatic intracranial hypotension: Report of two cases - Antonescu-Ghelmez, Dana; Butnariu, Ioana; Antonescu, Florian; Maier, Cristina; Moraru, Adriana; Bucur, Amanda Ioana; Anghel, Daniela Nicoleta; Tuţă, Sorin (Frontiers in Neurology, 2023)
Cerebrospinal fluid (CSF) leakage is considered the cause of spontaneous intracranial hypotension (SIH), an important etiology for new daily persistent headaches and a potentially life-threatening condition. Minor traumatic events rarely lead to CSF leakage, contrasting with iatrogenic interventions such as a lumbar puncture or spinal surgery, which are commonly complicated by dural tears. Most meningeal lesions are found in the cervicothoracic region, followed by the thoracic region, and rarely in the lumbar region, and extremely rarely in the sacral region. We describe two patients admitted to our hospital for severe headaches aggravated in the orthostatic position, with a recent history of minor trauma and sustained physical effort, respectively. In the first case, a bone fragment pierced an incidental congenital meningocele creating a dural fistula. An extensive extradural CSF collection, spanning the cervicothoracic region (C4–T10), was described in the second case. In both patients, the clinical evolution was favorable under conservative treatment.